2008
DOI: 10.1002/smr.363
|View full text |Cite
|
Sign up to set email alerts
|

Concept location in formal specifications

Abstract: When kept up-to-date, formal specifications can act as valid artifacts for maintenance tasks. However, their linguistic density and size impede comprehension, reuse, and change activities. Techniques such as specification slicing and chunking help in reducing the number of relevant lines of text to be considered, but they expect the point of change to be known a priori. This contribution presents a process model for concept location within formal Z-specifications. It also considers those situations when the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…[6, p.65] for Z), but for understanding the huge amount of text (and a lot of dependencies between different terms in the specification text) the help of tools [2] is needed. Moving away from the structure level, we do not have so much support from specification languages.…”
Section: Comprehending Specificationsmentioning
confidence: 99%
“…[6, p.65] for Z), but for understanding the huge amount of text (and a lot of dependencies between different terms in the specification text) the help of tools [2] is needed. Moving away from the structure level, we do not have so much support from specification languages.…”
Section: Comprehending Specificationsmentioning
confidence: 99%
“…Their idea is to look for predicates that are part of pre-and postconditions and to introduce "control" dependencies between them. Their idea has been refined and extended by Bollin [1] which also led to the development of an environment called V i Z that now supports reverse engineering of formal Z specifications by slicing, chunking and clustering techniques [3].…”
Section: Slice-based Transformation Processmentioning
confidence: 99%
“…Figure 1 presents the result for the transformation of the "Access Control Specification" as done by the V i Z environment. 3 V i Z generates an X M L file that can be imported by UML modeling tools like V isual Paradigm. 4 According to the mapping rules the system class contains all operations and the initialization schema as a constructor.…”
Section: Transformation Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Bollin showed that coupling and cohesion based measures can reasonably be mapped to formal Z specifications [3]. The basis for the calculation of all the measures is a graph that contains vertices (called primes) for all predicates and declarations of the specification, and arcs representing (reconstructed) control and data dependencies [2]. With such a graph as a basis, the following measures (defined for schemas ψ that are part of a specifications Ψ) are used in the remainder of this work: Semantics-based measures can be calculated by generating slices.…”
Section: Specification Measuresmentioning
confidence: 99%